Study of a conserved herpesvirus gene inducer of cell cycle arrest and IL-8 - Dias, Diogo Bernardes, 1991- (2015)
Tese de mestrado. Biologia (Microbiologia Aplicada). Universidade de Lisboa, Faculdade de Ciências, 2014